Clinical diagnosis and treatment of seven patients diagnosed pneumonia caused by Chlamydia abortus: a case series report - Wen, Ya; Du, Yanjia; Shi, Xiaoyan; Zeng, Zixiong (Frontiers in Medicine, 2024)
Background：Chlamydia abortus pneumonia is very rare in normal people. At present, there is a lack of clinical data on the clinical characteristics and diagnosis and treatment experience of patients with this type of infection. Our team had recently treated 7 cases of these patients.This study aims to comprehensively summarize and analyze the clinical characteristics and treatment methods of Chlamydia abortus pneumonia, and to provide clinical evidence for the diagnosis and treatment of Chlamydia abortus pneumonia.Methods: Clinical data were retrospectively collected from patients diagnosed with Chlamydia abortus pneumonia through metagenomic next-generation sequencing (mNGS) at